2012
DOI: 10.1186/2162-3619-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of hematopoietic stem cells for transplantation: current perspectives

Abstract: Hematopoietic stem cells (HSCs) are rare cells that have the unique ability to self-renew and differentiate into cells of all hematopoietic lineages. The expansion of HSCs has remained an important goal to develop advanced cell therapies for bone marrow transplantation and many blood disorders. Over the last several decades, there have been numerous attempts to expand HSCs in vitro using purified growth factors that are known to regulate HSCs. However, these attempts have been met with limited success for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Besides the generation of distinct hematopoietic lineages, the generation of HSCs from hiPSCs is a central purpose of biomedical research and transfusion medicine in particular [24,25]. Although significant efforts were done, true HSCs with long-term engraftment potential cannot be expanded indefinitely in vitro until now [26,27]. In contrast, undifferentiated hiPSCs can theoretically be expanded indefinitely in vitro while maintaining their pluripotency for all three germ layers; they can be stored, thawed, and differentiated into the desired tissue afterwards as well as bioengineered orgene-modified on demand.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the generation of distinct hematopoietic lineages, the generation of HSCs from hiPSCs is a central purpose of biomedical research and transfusion medicine in particular [24,25]. Although significant efforts were done, true HSCs with long-term engraftment potential cannot be expanded indefinitely in vitro until now [26,27]. In contrast, undifferentiated hiPSCs can theoretically be expanded indefinitely in vitro while maintaining their pluripotency for all three germ layers; they can be stored, thawed, and differentiated into the desired tissue afterwards as well as bioengineered orgene-modified on demand.…”
Section: Discussionmentioning
confidence: 99%
“…What knowledge can we obtain from developmental biology, and in particular, from analyzing hematopoietic development in the embryo which is of clinical relevance? One of the greatest challenges of modern hematology is the ex vivo expansion of human cord blood HSC as this has the potential to secure the safety of donors and solve the donor shortage in HSC transplantation for hematopoietic diseases [5152]. Various methods have been reported to improve the ex vivo expansion of human cord blood derived HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SALL4 has been shown to play an important role in maintaining ES cell (ESC) pluripotency and self-renewal properties. SALL4 is involved in the self-renewal of leukemic initiation and HSPC [14]. Moreover, recent data have shown that SALL4 plays an essential role in myeloid leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%